Occupational and socio-economic risk factors for giant cell arteritis: a nationwide study based on hospitalizations in Sweden. (November 2013) - Zöller, B; Li, X; Sundquist, J; Sundquist, K
<x xml:space="preserve">Abstract</x> Objectives: Socio-economic and occupational factors may contribute to risk of immune-mediated disorders. The importance of these factors in giant cell arteritis (GCA) is unknown. This is the first nationwide study with the aim of investigating possible associations between socio-economic status (SES)/occupation and hospitalization for GCA. Method: A nationwide database was constructed by linking Swedish census data to the Hospital Discharge Register to obtain data on all first hospitalizations with a main diagnosis of GCA in Swedish adults between 1970 and 2008. Standardized incidence ratios (SIRs) and 95% confidence intervals were calculated for different occupations. Three cohorts were defined based on 53 occupational titles recorded in Swedish census data in 1970, 1980, and 1990. Results: In individuals aged over 50 years, 3293 males and 4726 females were hospitalized with GCA. Only minor or inconsistent associations were observed for education and SES and GCA. Some occupations were associated with increased risk of GCA. However, the risks were modest or not consistent between the three cohorts investigated. Only male fishermen, whalers, and sealers had an SIR of > 2 (2.14). However, the risk of GCA was only increased in one cohort. Both women (0.83) and men (0.83) born outside Sweden had a lower risk of GCA. The adjustment variables hypertension, diabetes, chronic obstructive pulmonary disease (COPD), and coronary heart disease (CHD) were associated with higher risk of GCA. Conclusions: Occupation and SES are not strong risk factors for GCA. However, GCA was associated with co-morbidities and country of birth, calling for further studies.